DESIGN, DEVELOPMENT OF ADVANCES NANOFORMULATION ON DELIVERY FOR BRAIN FUNCTIONS AND BIOAVAILABILITY ACTIVITY FOR ANTI-VIRAL DRUG (International Journal of Food and Nutritional Sciences, 2022)
ABSTRACT- HIV, which causes AIDS, is one of the deadliest diseases and the sixth leading cause of death. The reported poor bioavailability of non-nucleoside reverse transcriptase inhibitors used to treat HIV infection is related to first pass metabolism, protein binding and enzyme metabolism. They are also less permeable to the blood-brain barrier. He biomimetic architecture, the ability to hijack host immune responses, continuous antigen shifting, and drafting are the major critical factors that are responsible for the unavailability of a concrete therapeutic regimen against viral infections. Further, inappropriate pharmacodynamic physicochemical and biological parameters such as low aqueous solubility, poor permeability, high affinity for plasm proteins, short biological half-lives, and fast elimination from the systemic circulation are the major critical factors that govern the suboptimal drug concentration at the target site that leads to the development of drug resistance. However, size, shape, charge, and surface topology of nanoparticles are the greater influential factors that determine target-specific drug delivery, optimum cellular uptake, degree of opsonization by the host immune cells, drug retention time, transcytosis, the extension of biological half-life, in vivo stability, and cytotoxicity. The review will enlighten the elaborative role of nanotechnology-based drug delivery and the major challenging aspect of clinical safety and efficacy. Various parameters of Efavirenz SLN gel were evaluated, such as gel temperature, pH, viscosity, light transmittance, muco-adhesive strength, diffusion, and in vitro and ex vivo dissolution studies. Drug release was found to be optimal for zero-order release kinetics (R2 = 0.3), suggesting that drug release is concentration-sensitive and diffusion-controlled. In vivo pharmacokinetic studies have shown that it is possible to successfully eradicate HIV in the brain and cure HIV patients after intranasal administration, and many of these problems are voluntarily overcome by the use of advanced anti-inflammatory drugs developed with nano-technology. These delivery systems carry antibodies in nanoparticles that can be made from synthetic or natural materials. However, due to health and environmental concerns, there is interest in developing antibiotics from natural products such as lipids.